Pengaruh Relokasi dan Lama Usaha Terhadap Tingkat Pendapatan Pedagang Pasar Angso Duo Kota Jambi - M.Firmansyah; Habriyanto Habriyanto; Ahmad Syukron Prasaja; Arsa Arsa; Hansen Rusliani; Ambok Pangiuk; Agustina Mutia (Lembaga Pengembangan Kinerja Dosen, 2023)
the effect of relocation and length of business on the income level of market traders Angso Duo Jambi City quantitative multiple linear regression analysis. A sample of 87 traders. The results of the relocation research have a positive effect, a significance value of 0.000 < 0.005 is obtained and the tcount (3.866) > ttable (1.667). The length of business partially has no effect and is not significant on the income of the Angso Duo Market traders, Jambi City, obtained a significance value of 0.324 > 0.05, the value of tcount (0.993) < smaller than ttable (1.667). The overall results of the study indicate that the significance value is 0.000 <0.05 and the Fcount (8.541) > Ftable (3.105). It can be concluded that there is a significant effect between relocation and length of business simultaneously on the income of the Angso Duo Market traders in Jambi City. Based on the results of the F test, it can be seen that the significance value for the effect of relocation (X1) and length of business (X2) simultaneously on the income of traders (Y) is 0.000 < 0.005 and the value of Fcount > Ftable (8.541 > 3.105). that H0 is rejected, it means that there is a significant effect between relocation and the length of simultaneous business together on the income of the Jambi Angso Duo Market traders. The Adjusted R Square (R2) value of income is influenced by relocation and length of business by 16.9% and the remaining 85.1%.